The use of a mobile app aimed at child healthcare education: a systematic review - Oliveira, Kelly Teles (2022)
Objective: Analyzing the use of a mobile application aimed at child healthcare education. Method: This is a thematic review of a quantitative approach, for the elaboration of the guiding question, the PICOS strategy was developed. The question is elucidated: Are mobile apps effective for child-based healthcare education? Data collection took place in 2017, in the following languages: Portuguese, English and Spanish from the VHL in the database: MEDLINE, in the PUBMED Portal, MEDLINE database, CAPES portal and CINAHL database. The MESH was used: “mobile applications,” “child” and “health” interconnected to the Boolean operators AND and OR. The inclusion criteria were being freely available full texts, published between 2014 and 2017, more scientific evidence research such as randomized clinical trials, case study and methodological research. Exclusion criteria: texts without fundamental references and papers that do not present abstracts in the databases. Results: A total of 53 publications were analyzed after the selected filters, including 15 articles according to categories: author, year, type of study and outcome. For the selection of the studies, the answer to the guide question and the evidence of the studies were considered. Most were randomized controlled trial and published between 2015 and 2017. Conclusion: It is needed to build, validate and apply mobile applications aimed at education and health promotion of children. These should be implemented and monitored in so that their effectiveness with regard to disease prevention and sustainability can be measured.